Pengaruh Keahlian Awak Kapal Terhadap . Pelayaran Pada Kapal Penumpang Roll On Roll Off - Himawan Aditya Pratama; Teguh Waskito Nugroho; Ivan Reyhansyah; Firstson Siom (Majalah Ilmiah Bahari Jogja, 2023)
Based on an analysis from the National Transportation Safety Committee or NTSC, so far 90 percent of marine accidents that have occurred in Indonesia are caused by the human factor, sometimes referred to as human error. So that the human factor is a very influential factor in ensuring the achievement of shipping safety. The purpose of this study was to determine the effect of crew expertise on shipping safety on roll on roll off (Ro-Ro) passenger ships at the Port of Tanjung Perak Surabaya. Case study: Roll on-roll off (Ro-Ro) passenger ship owned by PT. Main Ocean Dharma. This research was conducted using a quantitative approach. The data instrument used was a questionnaire with a sample of 103 respondents. The analysis used is simple linear regression analysis and correlation coefficient analysis by proving the hypothesis through the t test and f test. The results of the study show that the expertise of the crew has a significant and positive effect on shipping safety.